Vi bygger for livet: Medikalisering af den danske hospitalsarkitektur - Johannessen, Runa; Winkel Holm, Isak (K&K - Kultur og Klasse, 2021)
This article explores the “medicalization” of contemporary Danish hospital architecture. In the modern age, architecture and spatial design have been mobilized as remedies to further the health of the individual patient and of the population in general. In order to understand the present type of medicalization – as opposed to the early modern and classical modern types – we suggest a distinction between two kinds of biopolitics, in Michel Foucault’s sense of this term, respectively a biopolitics of bodies and a biopolitics of feelings. If the original medicalization was a somatic biopolitics, the contemporary medicalization could be described as an affective biopolitics, we claim. We focus on the ongoing boom in the construction of new hospitals in Denmark, discussing as empirical cases a planned hospital in Northern Zealand and a “multisensorial” delivery room in Herning, a Danish provincial town.